Personnel's Experiences of Phlebotomy Practices after Participating in an Educational Intervention Programme. (30th October 2014) - Bölenius, Karin; Brulin, Christine; Graneheim, Ulla H.
Abstract : Background . Blood specimen collection is a common procedure in health care, and the results from specimen analysis have essential influence on clinical decisions. Errors in phlebotomy may lead to repeated sampling and delay in diagnosis and may jeopardise patient safety. This study aimed to describe the experiences of, and reflections on, phlebotomy practices of phlebotomy personnel working in primary health care after participating in an educational intervention programme (EIP). Methods . Thirty phlebotomists from ten primary health care centres participated. Their experiences were investigated through face-to-face interviews. Findings were analysed using qualitative content analysis. Results . The participants perceived the EIP as having opened up opportunities to reflect on safety. The EIP had made them aware of risks in relation to identification procedures, distractions from the environment, lack of knowledge, and transfer of information. The EIP also resulted in improvements in clinical practice, such as a standardised way of working and increased accuracy. Some said that the training had reassured them to continue working as usual, while others continued as usual regardless of incorrect procedure. Conclusions . The findings show that EIP can stimulate reflections on phlebotomy practices in larger study groups. Increased knowledge of phlebotomy practices improves the opportunities to revise and maximise the quality and content of future EIPs. Educators and safety managers should reflect on and pay particular attention to the identification procedure, distractions from the environment, and transfer of information, when developing and implementing EIPs. The focus of phlebotomy training should not solely be on improving adherence to practice guidelines.